(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the legal framework and practical application of energy supply contracts in the Republic of Uzbekistan. The research analyzes the hierarchical system of normative acts regulating energy supply relations, from the fundamental provisions in the Civil Code to specialized industry legislation and subordinate regulations. The paper identifies the essential characteristics and terms of energy supply contracts, explores liability mechanisms for both suppliers and consumers, and examines current judicial practice in energy supply disputes. Special attention is given to modern trends in the development of energy legislation, including market liberalization, implementation of advanced metering technologies, tariff policy improvement, and renewable energy integration. The study also highlights existing challenges in the legal regulation of energy supply contracts and proposes prospective directions for improving the regulatory framework. The findings demonstrate that Uzbekistan’s energy contract regulation combines traditional approaches with innovative solutions aimed at enhancing the efficiency and competitiveness of the energy sector while maintaining a balance between the interests of energy suppliers and consumers.